Contributions of Antônio Gramsci's Caderno 12 to the understanding of political-pedagogical disputes in Brazilian special education (PerCursos, 2024)
We recognize the theoretical contribution of Antonio Gramsci to understand the social phenomena of the present time. We seek to reflect from the categorical mesh proposed by the author, specifically the categories organic intellectual, unitary school and integral education, present in notebook 12, on the policy proposals for Brazilian special education (2008 and 2020). We apprehend that the political propositions in the twenty-first century for Special Education, despite having differences between them, have in common that they do not propose a school that projects human emancipation. The organization of the organic intellectuals of the bourgeoisie around a school project that maintains social and educational inequalities is not similar to the proposal of a unitary school and integral education formulated by Gramsci. The propositions analyzed here disseminate a school project that does not have as its social function the cultural elevation of the masses, on the contrary, it works to promote subordination. The distancing of these political propositions from integral education, as a constituent of the unitary school, seems evident when, once again, the centrality of special education lies in techniques and resources for the development of isolated skills and competencies. Therefore, they arent based on knowledge systematized by humanity that would enable the formation of political leaders with a view to social transformation. We conclude that its contestation is carried out by an alternative project based on the deepening of the inequality of access to school education.
Keywords: organic intellectual; unitary school; integral education; educational policy; special education